The reality of counseling services as perceived by high school students in Medina, and their counseling needs - Alsenani, Sarah Awad Ahmmad; Yusef, Muhammad Abdulrahman (Journal of Educational and Psychological Sciences, 2022)
The aim of the study is to identify the level of services and counseling needs of high school students in Madinah, and the relationship between them, in addition to uncovering the significance of the statistically significant differences in the level of services and extension needs among secondary school students that are attributed to the academic grade. The relational was used, and the study community was formed. Of students, the age range of them ranges from، The total study sample consisted of (857)، high school students in Madinah in the second semester of the academic year 1441/1442 AH, they were randomly selected using the cluster sample method, and a questionnaire was built that includes the two axes of the study, the first axis measures the level of counseling services, the number of its (30)، divided into three domains (developmental, curative and preventive)،, and the second axis measures the level of instructional needs, the number of its (35)، was divided into four areas (psychological and emotional, social and family, academic and professional)، The validity and reliability of the two scales tool was verified by applying to the exploratory sample from outside the original research sample, the study reached the following results:1. It was found that the overall average of extension services was high, with an arithmetic mean value of (3.98)،, respectively: “development counseling services with a high degree (4.05)،, curative extension services with a high degree (3.94)، and a high degree of preventive (3.93)،2. It was found that the overall average of counseling needs with a low grade (2.57)، was in the following order: “professional with a medium degree (2.82)،, psychological and emotional needs with a medium degree (2.72)،, academic with a medium degree (2.62)،, then social and family with a low grade ((2.263. It was found that there are no statistically significant differences between the mean of services and extension needs attributed to the school grade, with the exception of professional needs in favor of female students in the third year of secondary compared to the first secondary school.4. It was found that there is an inverse correlation between the degrees of extension services and extension needs, amounting to(-0.44)،The study concluded with a set of recommendations: generalizing the experience of the reality of school counseling in Madinah to the rest of the educational regions in the Kingdom and emphasizing the need for continuity and follow-up in providing counseling services, which showed from the results of the study that they are available in a high degree.
Keywords: Counseling services; needs; high school students